UMPSA and TSTU enter first bilateral agreement to foster global academic cooperation - Nur Ezzati, Mohd Nasir (UMPSA, 2025)
TASHKENT, 21 April 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) has officially established its first international partnership with a public university in Uzbekistan, Tashkent State Technical University (TSTU).